1984
DOI: 10.1002/jsfa.2740350406
|View full text |Cite
|
Sign up to set email alerts
|

The production of ochratoxin A and citrinin in barley

Abstract: The production of ochratoxin A by Aspergillus ochraceus and of ochratoxin A and citrinin by Penicillium viridicatum growing on previously sterilised barley for 200 days at 5,lO and 20°C and a water activity of 0.85 is reported. A . ochraceus did not grow at 5"C, multiplied slowly at 10°C but did not produce toxin. At 20°C the organism multiplied more quickly and produced ochratoxin after 19 days, which slowly disappeared over the next 150 days. P. viridicatum grew slowly at 5°C but did not produce any toxin. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…When cool, the substrate was sliced aseptically and the pieces placed in sterile petri dishes (sample weight 8.0 f 0.5 9). The samples were inoculated, as described by Damoglou et al (1984).…”
Section: P R E P a R A T I O N Of T H E B R E A D A N A L O G U Ementioning
confidence: 99%
“…When cool, the substrate was sliced aseptically and the pieces placed in sterile petri dishes (sample weight 8.0 f 0.5 9). The samples were inoculated, as described by Damoglou et al (1984).…”
Section: P R E P a R A T I O N Of T H E B R E A D A N A L O G U Ementioning
confidence: 99%
“…(1996) revealed that ochratoxin A was detected in 98 of 295 samples of stored feedstuffs at levels ranging from 700 to 8000 ppb. Ochratoxin A appears frequently in cereals in several countries also accompanied by citrinin, penicillic acid and zearalenone (Damoglou et al . 1984; Grabarkiewicz‐Szczesna et al .…”
Section: Resultsmentioning
confidence: 99%
“…1985). It has been reported that cyclopiazonic acid, citrinin, rubratoxin B and patulin occurred naturally in stored grains (Damoglou et al . 1984; Pitt and Hocking 1985; Aziz and Youssef 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillic acid (49) M e w o ~O P. aurantiogriseum, P. vanbeymae, P. expansum, P. fennelliae, P. griseofulvum, P. madriti, P. puberulum, P. roquefortii, P. simplicissimum, P. thomii, P. viridicatum (P. M. Scott, 1977) (also Birkinshaw and GowHand, 1962;01ivigni and BuHerman, 1978;Mosbach, 1960) OH CH z Me Ac HOV Botryodiplodin (50) P. hirsutum (Fujimoto et at., 1980), P. roquefortii (Renauld et at., 1984) 6-Farnesyl-5, 7 -dihydroxy-4-methylphthalide (51) P. brevicompactum (Canonica et at., 1971) Mycochromenic acid (54) P. brevicompactum (Campbell et at., 1966;Bird and Campbell, 1982b;Colombo et aI., 1982) For mycophenolic acid, also: P. paxilli , P. roqueJortii (Lafont et at., 1979), P. otivicotor (Oxford and Raistrick, 1933) 3,7-Dimethyl-8-hydroxy-6-methoxy isochroman (61) P. citrinum (Cox et at., 1979) Canescin (62) P. canescens R) = H, R2 = H: Scott, 1977); P. viridicatum (P. M. Scott, 1977;Damoglou et al, 1984); P. purpurescens, P. roquefortii, P. spinulosum (Leistner and Pitt, 1977); P.janthinellum (Czech patent, 1982) Me P. viridicatum (Hutchison et al, 1971) 1 R = H: Ochratoxin A (72) P. viridicatum (van Walbeek et ai., 1969;van cler Merwe et al, 1965;Damoglou et al, 1984); P. aurantiogriseum, P. purpurescens, P. variabile, P.…”
Section: Coohmentioning
confidence: 99%